Trajetória educacional de mulheres em assentamentos de reforma agrária na região tocantina-MA - Amorim, Elisângela Santos de (2007)
The inquiry approaches the question of countrywomen and your education in settlement of the Agrarian Reformation in the Tocantina region - MA. We carry through study on the trajectory of countrywomen in search of recognition of the category of agricultural worker woman, focusing the fights of the movements in favor of the education of the field in Brazil, in Maranhão and the Tocantina region, emphasizing the protagonists women of this process. Study of qualitative character, developed with the objective to study as the gender relations they intervened with the educational trajectories of adult and young countrywomen. It brings theoretical contributions of Scott, Moscovici, Jodelet, Sá, Silva, Louro, Nobre, in the perspectives of gender and social representation. Interviews in the period of 2005/2007 had been carried through, using the methodological approach of the verbal history, through halfstructuralized interviews. The stories had been submitted to the technique of thematic analysis of content, having the categories gender and social representation for the interpretations. It tells to the importance of the National Program of Education in the Agrarian Reformation - PRONERA in the Tocantina region and its contribution for the rise of the schooling of that parcel of the population. It approaches the relations lived deeply for the countrywomen, from the relations of gender and your social representations of countrywomen and learned woman. It focuses aspects of the trajectories of life of these women, where are explicit and many times implicit the difficulties in the search for schooling. At last the study stands out the influence of the relations of gender in the elaboration of the social representations in its specific conditions.